Editor's Note - Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
The JCSH, succeeding The Rangsit Journal of Social Science and Humanity (RJSH), continues to focus on publishing research works of various contemporary issues in social sciences and humanities. In this issue, we are very pleased to present eight (8) research articles from various academic disciplines. In the first article, Patteera Pantaratorn, Jittasak Putjorn and Wongladda Weerapaiboon studied the barriers to low carbon tourism development in Thailand, focusing on the supply side. By using both qualitative and quantitative research methods, the authors concluded that the barriers to low carbon tourism development are structure constraints (such as inadequate budgets and inadequate tourism facilities), intrapersonal constraints (such as deficiency in knowledge and inadequate awareness), and interpersonal constraints (such as inadequate coordination and cooperation). Next, Thanaphon Boonyaratanakornkit and Nutthathirataa Withitwinyuchon evaluated qualitatively the effectiveness and efficiency of the Let’s Go Halves Program, an economic stimulus measure of the Thai government. The authors found that this program was effective and efficient in stimulating the economy and assisting those affected by the COVID-19 outbreak in 2020-2021, despite challenges with program accessibility, technical compatibility, inequity in program participation, and program transparency.